PENGARUH VARIABEL MAKROEKONOMI TERHADAP IHSG PADA PERIODE PEMULIHAN EKONOMI PASCA COVID-19 TAHUN 2020-2024 - Nur Aiga Mawarni; Irfan Gaffar Adnan; Fahmaninda Listiyani (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
The post-pandemic dynamics of the IHSG reflect the capital market’s vulnerability to shifts in macroeconomic indicators, making it necessary to analyze the factors influencing them. This quantitative study evaluates the impact of exchange rates, interest rates, inflation, GDP, and FDI on the IHSG in Indonesia for the 2020-2024 period. It utilizes secondary data in the form of quarterly time series obtained from the Bank of Indonesia (BI), the Central Statistics Agency (BPS), Investing.com, and Trading Economics. Data analysis was conducted using multiple linear regression with the EViews 13 software, along with a series of assumption tests and statistical analyses. The results of the partial tests confirm that exchange rates, interest rates, GDP, and FDI have a significant impact, while inflation has a non-significant impact. Collectively, all independent variables account for 77.1% of the variation in the IHSG. This finding underscores the importance of macroeconomic stability as the foundation for investment decisions and the formulation of capital market policies.